"=i\\begin{vmatrix}\n \\mu_2 & \\nu_2 \\\\\n \\mu_3 & \\nu_3\n\\end{vmatrix}-j\\begin{vmatrix}\n \\lambda_2 & \\nu_2 \\\\\n \\lambda_3 & \\nu_3\n\\end{vmatrix}+k\\begin{vmatrix}\n \\lambda_2 & \\mu_2 \\\\\n \\lambda_3 & \\mu_3\n\\end{vmatrix}"
"=\\begin{vmatrix}\n \\lambda_1& \\mu_1 & \\nu_1 \\\\\n \\lambda_2& \\mu_2 & \\nu_2 \\\\\n\\lambda_3& \\mu_3 & \\nu_3\n\\end{vmatrix}"
(b)
Switching Property:
The interchange of any two rows (or columns) of the determinant changes its sign.
"=-\\begin{vmatrix}\n \\lambda_2& \\mu_2 & \\nu_2 \\\\\n \\lambda_1& \\mu_1 & \\nu_1 \\\\\n\\lambda_3& \\mu_3 & \\nu_3\n\\end{vmatrix}=\\begin{vmatrix}\n \\lambda_1& \\mu_1 & \\nu_1 \\\\\n \\lambda_2& \\mu_2 & \\nu_2 \\\\\n\\lambda_3& \\mu_3 & \\nu_3\n\\end{vmatrix}="
(c)
"r'(t)=6ti+3t^2j+k"
"r''(t)=6i+6tj+0k"
"r\\times r'=\\begin{vmatrix}\n i& j & k \\\\\n 3t^2-4& t^3 & t+2 \\\\\n6t& 3t^2 & 1\n\\end{vmatrix}="
"=i\\begin{vmatrix}\n t^3 & t+2\\\\\n 3t^2 & 1\n\\end{vmatrix}-j\\begin{vmatrix}\n 3t^2-4 & t+2 \\\\\n 6t & 1\n\\end{vmatrix}+k\\begin{vmatrix}\n 3t^2-4 & t^3\\\\\n 6t & 3t^2\n\\end{vmatrix}="
"=(t^3-3t^3-6t^2)i-(3t^2-4-6t^2-12t)j+"
"+(9t^4-12t^2-6t^4)k="
"=(-2t^3-6t^2)+(3t^2+12t+4)j+(3t^4-12t^2)k"
Comments
Leave a comment